The energy bus 10 rules to fuel your life, work, and team with positive energy - Gordon, Jon. (Hoboken John Wiley & Sons, 2007)
It's Monday morning and George walks out the front door to his car and a flat tire. But this is the least of his problems. His home life is in shambles and his team at work is in disarray. With a big new product launch coming up in 2 weeks for the NRG-2000 he has to find a way to get it together or risk losing his marriage and job. Forced to take the bus to work, George meets a unique kind of bus driver and an interesting set of characters (passengers) that over the course of 2 weeks share the 10 rules for the ride of his life... and attempt to help him turn around his work and team and save his job and marriage from an almost inevitable destruction."
Includes index.
Keywords: Teams in the workplace--Management.